Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1007/s40037-020-00623-y
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the wisdom of the crowd: health professions’ educators meet at a virtual world café

Abstract: Background Conversations about educational challenges and potential solutions among a globally and culturally diverse group of health professions’ educators can facilitate identity formation, mentoring relationships and professional network building. The COVID-19 pandemic has made it even more important to co-create and disseminate knowledge, specifically regarding online and flexible learning formats. Approach Based on the principles of social learning, we combined speed mentoring and world café formats to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 16 publications
(22 reference statements)
1
22
0
1
Order By: Relevance
“…Thus, the World Café method can be relatively easily adapted for use online. A recent study, conducted by McKimm et al [ 21 ] during the COVID-19 pandemic, demonstrated the feasibility of using this method for health educators from across the world to discuss educational initiatives to promote online learning [ 21 ]. The researchers reported several issues with the method that related primarily to technological difficulties, audience size, and different time zones [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the World Café method can be relatively easily adapted for use online. A recent study, conducted by McKimm et al [ 21 ] during the COVID-19 pandemic, demonstrated the feasibility of using this method for health educators from across the world to discuss educational initiatives to promote online learning [ 21 ]. The researchers reported several issues with the method that related primarily to technological difficulties, audience size, and different time zones [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Virtual curricula often limit organic conversations and introductions between peers. In our experience, online meeting platforms are not designed to accommodate multiple conversations in a meeting due to audio and visual limitations and are more conducive to single-speaker presentations [7]. This contrasts with an in-person encounter in which new classmates typically get to know one another through casual introductions, which are vital to students becoming comfortable discussing and sharing opinions with one another.…”
Section: Tip 2: Establish Small Groups To Bolster the Group As A Wholementioning
confidence: 99%
“…1,4,15 The three core elements of domain, practice and community remain applicable to virtual CoPs 8 and can contribute to PIF and scholarship. 1,15,18 SoMe platforms can ease development of virtual CoPs, allowing professionals from diverse contexts and cultures to interact with each other synchronously or asynchronously, while minimising barriers caused by hierarchy, language skills, or divergent time zones. 1,12,15 As we emerge from the COVID-19 pandemic and begin to envision the future of health professions education, networks formed during the pandemic (through shared interests and need for connectivity) will be just as relevant postpandemic.…”
Section: Being Part Of An Exciting Communitymentioning
confidence: 99%
“…1,12,15 As we emerge from the COVID-19 pandemic and begin to envision the future of health professions education, networks formed during the pandemic (through shared interests and need for connectivity) will be just as relevant postpandemic. 15,16,18 However, groups should reflect on lessons learned that are relevant postpandemic, leaders should retain their adaptive edge and individuals leading the formation of CoPs should attend to diversity and inclusivity and move well away from just extending their local, regional or national insular community. 10 Knowledge sharing and collaborations should be inclusive of multiple cultural and societal perspectives, and diversity can be facilitated by SoMe engagement.…”
Section: Being Part Of An Exciting Communitymentioning
confidence: 99%
See 1 more Smart Citation